The Effects of Tempering and Cooling Media on The Strength of Hadfield Steel - Sukmayanti, Putri; Tjahjono, Arif; Paristiawan, Permana Andi (Physics Study Programme, Faculty of Science and Technology UIN Syarif Hidayatullah Jakarta, 2023)
Hadfield steel is a steel known for its good toughness, but it often experiences damage due to excessive loads. In this study, an analysis of the heat treatment process was conducted on Hadfield steel to enhance its strength through homogenization at a temperature of 850°C and tempering at 600°C with a holding time of 30 minutes, followed by a rolling process with a 20% reduction. The data analysis results indicate that the sample cooled using water as the cooling media produced the most optimum strength. This is evident from its tensile strength value, which reached 941 MPa, with a grain size of 3.51 µm. Although its hardness value 351.98 BHN is slightly lower compared to the sample cooled with air, the difference is not significant. The metallographic observations show that there is a phase change in the sample. Initially, the sample only had an austenite phase during the homogenization process. However, after undergoing tempering, there is a phase change to austenite, ferrite, martensite, and carbide phases. This change will result in an increase in the strength of Hadfield steel.